2000
DOI: 10.1063/1.1322629
|View full text |Cite
|
Sign up to set email alerts
|

Second-harmonic and sum-frequency imaging of organic nanocrystals with photon scanning tunneling microscope

Abstract: Sum-frequency generation in doubly resonant GaP photonic crystal nanocavities Appl. Phys. Lett. 97, 043103 (2010); 10.1063/1.3469936Near-field microscopy and spectroscopy of third-harmonic generation and two-photon excitation in nonlinear organic crystals Second-harmonic generation and sum-frequency generation with photon scanning tunneling microscopy and shear-force detection are used to map the nonlinear optical response and the surface topograph of N-͑4-nitrophenyl͒-͑L͒-prolinol crystals with a subdiffracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…Molecular specific imaging on non-centrosymmetric molecular interfaces and domains [1][2][3][4][5][6][7][8][9][10][11][12] is crucial for understanding structures and dynamics on many inhomogeneous systems, such as chemical reactions on heterogeneous catalysts, 13 protein interactions with lipid bilayers, 14 structure of optical metamatials, 15 and formation of structure color materials. 16 By spatially resolving interfaces and domains, microscopy could obtain domain specific knowledge and mitigate ensemble averaging.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular specific imaging on non-centrosymmetric molecular interfaces and domains [1][2][3][4][5][6][7][8][9][10][11][12] is crucial for understanding structures and dynamics on many inhomogeneous systems, such as chemical reactions on heterogeneous catalysts, 13 protein interactions with lipid bilayers, 14 structure of optical metamatials, 15 and formation of structure color materials. 16 By spatially resolving interfaces and domains, microscopy could obtain domain specific knowledge and mitigate ensemble averaging.…”
mentioning
confidence: 99%
“…Using this code, we can differentiate domains with various molecular conformations, which would otherwise be difficult to distinguish using optical imaging techniques 41 or homodyne VSFG microscopes. [4][5][6][7][8][9][10][11][12] We implemented this phase-stable collinear HD VSFG microscope to study a guest-host molecular self-assembly 42 spin-coated on gold. We found that the self-assembly contains non-centrosymmetric domains at sizes from about 20 to 100 μm 2 , and there are mainly two types of domains, which have opposite molecular alignment relative to each other.…”
mentioning
confidence: 99%
“…Surface SHG Enhancement Induced by Specific Surface Morphology. Surface plasmon-assisted SHG enhancement from metal clusters has been reported for several systems, [32][33][34] including Au nanocluster-deposited Si(111) surfaces. Suni and co-workers [35][36][37][38] studied deposition kinetics of Au nanoclusters grown on p-Si(111) by means of surface plasmon-enhanced SHG and noncontact AFM.…”
Section: Modification Of the Sh-ra Pattern By Cu Depositionmentioning
confidence: 99%
“…In a similar context, it should be highlighted the experiment realized by the Prasad group on nonlinear excitation of organic nanocrystals with a photon scanning tunneling microscope. [14] Our results are discussed in terms of efficiency and polarization properties. Further information about individual nanoparticles' orientation and coherent emission are derived within the defined image defocusing framework first …”
Section: Introductionmentioning
confidence: 99%